miR-21, miR-29a, and miR-106b serum and tissue biomarkers with diagnostic potential in metastatic testicular cancer - Újfaludi Zsuzsanna (SCIENTIFIC REPORTS, 2024)
The imperative need for sensitive and precise tools is underscored in cancer diagnostics, with biomarkers playing a pivotal role in facilitating early detection and tumor diagnosis. Despite their classical pathological classification, testicular tumors lack valuable markers, emphasizing the necessity to identify and apply serum tumor markers in clinical management. Unfortunately, existing biomarkers exhibit limited sensitivities and specificities. Recent years have witnessed the discovery of novel RNA molecules, presenting a potential breakthrough as diagnostic tools and promising biomarkers. This report presents compelling evidence supporting the detection of early testicular cancer by applying a set of nine microRNAs (miRNAs), establishing them as valuable serum biomarkers for diagnosis. We developed a standardized serum-based measurement protocol and conducted comprehensive statistical analyses on the dataset to underscore the diagnostic accuracy of the miRNA pool. Notably, with a sensitivity exceeding 93%, miR-21, miR-29a, and miR-106b surpass classical serum tumor markers in the context of testicular cancer. Specifically, these miRNAs are poised to enhance clinical decision-making in testicular cancer detection and hold the potential for assessing tumor growth in monitoring chemotherapy outcomes.